Double-edged sword: Understanding the localized effect of foreign direct investment inflow in conflict settings - Lorenzo Crippa; Laura Saavedra-Lux (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We analyse how inward foreign direct investment (FDI) received amid ongoing violence shapes armed conflict. We argue that FDI affects patterns of violence by influencing the state's counterinsurgency strategy. To prevent disinvestment, governments strive to capture territory linked to investment. Yet, heightened military presence in areas close to FDI projects reinforces rebel group reliance on irregular warfare, thus amplifying civilian victimization as a tool to elicit cooperation or enforce control. Using subnational, georeferenced data on FDI and armed conflict in African countries from 2003 to 2019, we find that conflict events within 5-10 km of a foreign investment see 25 per cent more civilian casualties. The effect is largely driven by increased rebelled, deliberate civilian targeting, and amplified for extractive FDI. We address endogeneity concerns by comparing conflict dynamics between areas that experience an investment with areas that will experience one in the future within the same country-year. Our findings underscore the influence of globalization on political stability.
Keywords: O16; Q34; 330; FDI; armed conflict; civilian victimization